Kalymnos Island, SE Aegean Sea: From Fishing Sponges and Rock Climbing to Geotourism Perspective - Zafeiropoulos, George; Hara Drinia (Heritage, 2021)
The island of Kalymnos, located in the Dodecanese island complex in the SE Aegean, is known for its sponge fishing but also for its world-famous climbing fields. Indeed, the island is considered the “Mecca” of climbers. Nevertheless, Kalymnos is characterized by moderate tourist traffic and lack of tourism infrastructure. The planning and development of geotourism can be a driving force for the economic sustainability of the island. In this study, the possibility of developing the innovative and alternative form of geotourism on the island of Kalymnos is explored. Kalymnos is characterized by numerous caves and steep slopes which can be geotopes attractive to visitors. Six caverns and two climbing fields were analyzed as part of our investigation. For the quantitative assessment of the geosites three factors are considered: the potential educational use (PEU), the potential touristic use (PTU), and the degradation risk (DR). The quantitative evaluation in combination with a SWOT analysis showed that there is indeed a possibility of promotion and development of geotourism in combination with the protection of the island’s geotopes. This will give additional impetus to the economy of Kalymnos. However, the lack of awareness from local authorities and residents is evident. The need for training in matters related to the geological heritage is necessary. In this way, there will be geotourism development, contributing positively to the economic prosperity and sustainability of the island.